2020
DOI: 10.1111/jvs.12915
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of initial plant establishment in salt marsh communities

Abstract: Questions How are dispersal processes, abiotic and biotic interactions determining the initial salt marsh plant community establishment and development when connectivity is different? We aim to answer this question by analysing the spatial and temporal patterns of plant establishment along an environmental gradient at two connectivity settings. Location Back‐barrier salt marsh and tidal flats of Spiekeroog, northwest Germany. Methods We established an experiment along a saltmarsh elevation gradient with bare s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…Using these data, it could be shown that highest species diversity and fine root biomass can be found at the intermediate inundation frequency and zonation of salt marsh vegetation reflects the availability of water sources along the inundation gradient (Redelstein et al, 2018a,b). Similarly, the initial colonization of vascular plants on salt marshes depended on the environmental conditions mediated by the elevation above mean sea level with most individuals colonizing the mid elevations, but higher elevations supporting larger species richness of initial communities (Lõhmus et al, 2020).…”
Section: Biodiversity-ecosystem Functioning (Bef) Field Experimentsmentioning
confidence: 96%
“…Using these data, it could be shown that highest species diversity and fine root biomass can be found at the intermediate inundation frequency and zonation of salt marsh vegetation reflects the availability of water sources along the inundation gradient (Redelstein et al, 2018a,b). Similarly, the initial colonization of vascular plants on salt marshes depended on the environmental conditions mediated by the elevation above mean sea level with most individuals colonizing the mid elevations, but higher elevations supporting larger species richness of initial communities (Lõhmus et al, 2020).…”
Section: Biodiversity-ecosystem Functioning (Bef) Field Experimentsmentioning
confidence: 96%
“…We highlight the need to distinguish between the adult niche and the regeneration niche to understand better how the abiotic filter works (Del Vecchio et al, 2020, this issue; Lõhmus et al, 2020, this issue). The difference between the adult niche and the regeneration niche (Grubb, 1977) determines whether under certain environmental conditions, a species is capable of generative reproduction or only of surviving and possibly of vegetative reproduction.…”
Section: Germination and Recruitmentmentioning
confidence: 99%
“…The encroachment of pioneer halophytes capable of thriving in highly hypoxic and hypersaline soils facilitates sediment accumulation, ameliorate physical stresses, and promote further marsh growth thanks to the ability of these critical foundation species (sensu Dayton, 1975) to eco-engineer their habitats (Ranwell, 1972;Jones et al, 1994;Bruno, 2000;Bruno and Kennedy, 2000;Crain and Bertness, 2006;Morris, 2007;Vandenbruwaene et al, 2011;Da Lio et al, 2013;Marani et al, 2013;Lõhmus et al, 2020;van Regteren et al, 2020). Once foundation species are established, a network of emergent vegetation organized into recurrent zonation patterns develops along the gradients of elevation and salinity that characterize tidal wetlands (Pennings and Callaway, 1992;Belluco et al, 2006;Marani et al, 2006) (Figures 1A,B).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is often overlooked that biological dispersal and competition in tidal marshes are density-dependent processes, i.e., they are a function of local population size, as well as habitat quality and size (Bertness and Ellison, 1987;Ellison, 1987;Bouma et al, 2009;Balke et al, 2017;Lõhmus et al, 2020;Bertassello et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation